TINJAUAN YURIDIS TERHADAPKEJAHATAN KEAMANAN NEGARA DALAM MEDIA SOSIAL INTERNET - Syawal Amry Siregar; Lestari Victoria Sinaga (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2020)
Privacy and State Secrets can be destroyed by cyber secret scientists who can cause widespread unrest in society. This research uses a normative juridical method that is reviewing the laws and regulations namely Law number 19 of 2016 concerning ITE (Electronic Information and Transactions), Law No. 3 of 2002 concerning National Defense. Based on the results and conclusions obtained, the trend of the threat of cyber attacks will develop in accordance with the development of information technology so that Law No. 3 of 2002 concerning National Defense can be provided about defense in the State defense system consisting of military and non-military security that also uses cyber.